Interplay between the surface adsorption and solution-phase behavior in dialkyl chain cationic-nonionic surfactant mixtures - Tucker, I (Langmuir : the ACS journal of surfaces and colloids, 2009)
Neutron reflectivity, NR, and surface tension have been used to study the adsorption at the air-solution interface of mixtures of the dialkyl chain cationic surfactant dihexadecyl dimethyl ammonium bromide (DHDAB) and the nonionic surfactants monododecyl triethylene glycol (C12E3), monododecyl hexaethylene glycol (C12E6), and monododecyl dodecaethylene glycol (C12E12). The adsorption behavior of the surfactant mixtures with solution composition shows a marked departure from ideal mixing that is not consistent with current theories of nonideal mixing. For all three binary surfactant mixtures there is a critical composition below which the surface is totally dominated by the cationic surfactant. The onset of nonionic surfactant adsorption (expressed as a mole fraction of the nonionic surfactant) increases in composition as the ethylene oxide chain length of the nonionic cosurfactant increases from E3 to E12. Furthermore, the variation in the adsorption is strongly correlated with the variation in the phase behavior of the solution that is in equilibrium with the surface. The adsorbed amounts of DHDAB and the nonionic cosurfactants have been used to estimate the monomer concentration that is in equilibrium with the surface and are shown to be in reasonable qualitative agreement with the variation in the mixed critical aggregation concentration (cac)